2014
DOI: 10.1371/journal.pone.0115401
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg3 Inhibits Melanoma Cell Proliferation through Down-Regulation of Histone Deacetylase 3 (HDAC3) and Increase of p53 Acetylation

Abstract: Malignant melanoma is an aggressive and deadly form of skin cancer, and despite recent advances in available therapies, is still lacking in completely effective treatments. Rg3, a monomer extracted from ginseng roots, has been attempted for the treatment of many cancers. It is reported that the expressions of histone deacetylase 3 (HDAC3) and p53 acetylation correlate with tumor cell growth. However, the antitumor effect of Rg3 on melanoma and the mechanism by which it regulates HDAC3 expression and p53 acetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 48 publications
2
63
0
Order By: Relevance
“…The HDAC inhibitors vorinostat, romidepsin and belinostat are currently approved for the treatment of relapsed or resistant cutaneous and peripheral T-cell lymphomas [24]. In solid organ malignancies, these agents are less effective as monotherapy [24]; currently, numerous clinical trials for other haematological and solid organ malignancies [41] are using HDAC inhibitors combined with other chemotherapeutic agents [42]. In some tumours, a strong level of HDAC expression is suspected to be indicative of a positive response to HDAC inhibition [24].…”
Section: Discussionmentioning
confidence: 99%
“…The HDAC inhibitors vorinostat, romidepsin and belinostat are currently approved for the treatment of relapsed or resistant cutaneous and peripheral T-cell lymphomas [24]. In solid organ malignancies, these agents are less effective as monotherapy [24]; currently, numerous clinical trials for other haematological and solid organ malignancies [41] are using HDAC inhibitors combined with other chemotherapeutic agents [42]. In some tumours, a strong level of HDAC expression is suspected to be indicative of a positive response to HDAC inhibition [24].…”
Section: Discussionmentioning
confidence: 99%
“…Ginsenoside Rg3 has diverse pharmacological effects in vitro and in vivo via the activation or repression of the expression of different genes. Previous studies have reported that ginsenoside Rg3 inhibits cancer cell proliferation and induces apoptosis by decreasing the expression of histone deacetylase 3 (1), epidermal growth factor receptor (2), fucosyltransferase IV (3) and vascular endothelial growth factor (VEGF) (4), and upregulates the protein expression of pro-apoptotic P53 (1), caspase-3, caspase-8 and caspase-9 (5). Ginsenoside Rg3 has been shown to enhance the radiosensitivity of human esophageal carcinoma cells by downregulating the expression of VEGF and hypoxia inducible factor-1α (6), and ginsenoside Rg3 may have a neuroprotective function in the rat hippocampus via the inhibition of hippocampus-mediated N-methyl-D-aspartate receptor activation (7).…”
Section: Introductionmentioning
confidence: 99%
“…Epigallocatechin gallate inhibited the proliferation and induced the apoptosis of ovarian cancer SKOV3 cells in a dose-and time-dependent manner by downregulated expression of AQP5, which may be associated with nuclear transcription factor, nuclear factor kappa B (NF-kB). 59 Ginsenoside Rg3 (Rg3), one of the bioactive extracts found in ginseng root, was reported to have anticancer activity in various cancer models such as malignant melanoma 60 and esophageal SCC. 61 It is also reported that Rg3 effectively suppressed migration of PC-3M cell, which was a highly metastatic prostate cancer cell line, by downregulating AQP1 expression through p38 mitogen-activated protein kinases pathway and some transcription factors acting on the AQP1 promoter.…”
Section: The Traditional Chinese Medicinesmentioning
confidence: 99%